The effect of nutritional and lifestyle education intervention program on nutrition knowledge, diet quality, lifestyle, and nutritional status of Croatian school children - Kendel Jovanović, Gordana; Janković, Suzana; Pavičić ŽeŽelj, Sandra (Frontiers in Sustainable Food Systems, 2023)
Introduction: Nutrition education during adolescence has proven effective in increasing knowledge, attitudes, and practices in the diet. The Mediterranean diet has proven health benefits and is proposed as a model of a sustainable diet, beneficial for health and the environment. Its promotion with the educational program can have a significant effect on improvements in nutrition knowledge, diet quality, and nutritive status of adolescents for their healthy adulthood. Objective: To investigate the effect of the educational program on the nutrition knowledge, diet quality, lifestyle, and nutritional status of school children from the Littoral part of Croatia. Methods: An education-based intervention study was carried out on 2709 schoolchildren aged 10–12 years (educated/control group: 2617/92). The questionnaire about socio-demographic, anthropometric, dietary, physical activity, screen time and sleep habits, and nutrition knowledge was assessed at the baseline and after 6 to 9-month follow-up for the medium-term effect of education. Nutrition knowledge was done after three weeks for the short-term education effect assessment. Results: Educated schoolchildren achieved a significant increase in nutrition knowledge (+75.5%, p<0.001) expressed as a short-term effect of the education and maintained at the 6 to 9-month follow-up (+66.8%, p<0.001). Follow-up children significantly improved their nutritional status (underweight -56.6%; normal weight 24.8%; overweight -22.1%; obesity -57.5%; all p<0.001) and physical activity engagement (+13.2, p<0.001). The proportion of children with a diet highly adhering to the Mediterranean diet significantly doubled (+105.0%, p<0.001). Those children with follow-up highest nutrition knowledge significantly improved their nutritional status (+218.9%, p<0.001), used organized sports (+204.7%, p=0.005), and had a diet that highly adhered to the MD (+291.8%, p<0.001). Conclusion: Significantly good medium-term effect of education-based nutrition and lifestyle intervention program on nutrition knowledge, diet quality, lifestyle, and nutritional status of schoolchildren aged 10 to 12 years was shown. The educational program promoted a Mediterranean diet and lifestyle as a healthy and sustainable way of living, important for children's future health and wellbeing. New research-based approaches are needed for making children more aware and capable of handling sustainable living complexity.